Nontuberculous Mycobacteria Prevalence in Aerosol and Spiders' Webs in Karst Caves: Low Risk for Speleotherapy - Hubelova, Dana; Ulmann, Vit; Mikuska, Pavel; Licbinsky, Roman; Alexa, Lukas; Modra, Helena; Gersl, Milan; Babak, Vladimir; Weston, Ross Tim; Pavlik, Ivo (Microorganisms, 2021)
A total of 152 aerosol and spider web samples were collected: 96 spider's webs in karst areas in 4 European countries (Czech Republic, France, Italy, and Slovakia), specifically from the surface environment (n = 44), photic zones of caves (n = 26), and inside (aphotic zones) of caves (n = 26), 56 Particulate Matter (PM) samples from the Sloupsko-Sosuvsky Cave System (speleotherapy facility; n = 21) and from aerosol collected from the nearby city of Brno (n = 35) in the Czech Republic. Nontuberculous mycobacteria (NTM) were isolated from 13 (13.5%) spider's webs: 5 isolates of saprophytic NTM (Mycobacterium gordonae, M. kumamotonense, M. terrae, and M. terrae complex) and 6 isolates of potentially pathogenic NTM (M. avium ssp. hominissuis, M. fortuitum, M. intracellulare, M. peregrinum and M. triplex). NTM were not isolated from PM collected from cave with the speleotherapy facility although mycobacterial DNA was detected in 8 (14.3%) samples. Temperature (8.2 °C, range 8.0-8.4 °C) and relative humidity (94.7%, range 93.6-96.6%) of air in this cave were relatively constant. The average PM2.5 and PM10 mass concentration was 5.49 µg m-3 and 11.1 µg m-3. Analysed anions (i.e., F-, Cl-, NO2-, SO42-, PO43- and NO3-) originating largely from the burning of wood and coal for residential heating in nearby villages in the surrounding area. The air in the caves with speleotherapy facilities should be monitored with respect to NTM, PM and anions to ensure a safe environment.
Keywords: mycobacteria other than tuberculosis (MOTT); risk groups of microorganisms; non-tuberculous mycobacteria (NTM); saprophytic environmental mycobacteria; cave airflow; asthma therapy; underground therapy